Maternal-Fetal Relationship in Pregnancy After Perinatal Loss Among African American Women - (:unkn) unknown (My University, 2020)
Purpose: Explore perceptions of chronic stressors of African American women before, during and after a perinatal loss and during a subsequent pregnancy to a loss. Explore the perceptions of stress and loss and its association with establishing a positive maternal-fetal relationship early in subsequent pregnancies to a perinatal loss. Design: Qualitative study using thematic analysis was conducted. Setting: Participants were recruited from clinics where women receive care, perinatal loss support groups, community centers, churches, hair salons, and social media throughout the United States. Participants: African American women (n=22), who reported a history of pregnancy loss at >14 weeks gestation or a newborn Methods: Data was collected using semi-structured individual interviews and was analyzed using Black feminist thought and intersectionality alongside a life-course perspective. Results: Women identify complex stressors before, during, and after their perinatal loss and in subsequent pregnancies to their loss. Their mental well-being was at the center of their narratives. Women experienced heightened anxiety and fear as they entered into a subsequent pregnancy to her loss. They admitted these emotions created a delay in establishing a relationship with her fetus until later in pregnancy. Women also perceived experiencing racial discrimination by their healthcare provider at some point over the course of their perinatal loss. Women used comforting coping strategies which included social support, religious and spiritual beliefs, and practices to help manage their stress. Conclusion: Women placed chronic stress and their mental well-being at the center of their narratives as powerful indicators that frequent prenatal assessment and early follow-up care is needed from healthcare providers after perinatal loss and during a subsequent pregnancy to a loss.
Keywords: African American women; Black feminist thought; Intersectionality; Life-course perspective; Maternal-fetal relationship; Perinatal loss